Study of the current state and prospects of artificial intelligence in cybersecurity - Golikov, Yu.L. (Radiotekhnika, 2025)
In the modern world, with the development of new technologies, artificial intelligence (AI) in cybersecurity has become an integral component. Therefore, studying its advantages, risks, and potential use cases is a highly relevant research topic. In current digital environment, where cyber threats are becoming increasingly sophisticated, the implementation of AI technologies significantly enhances the effectiveness of security systems by enabling automated threat detection and response. In this study the main applications of AI in cybersecurity were examined, including threat detection, malware analysis, cryptographic security enhancement, phishing protection, and attack prediction. One of the key aspects is the integration of AI into Security Information and Event Management (SIEM) systems, which analyze vast amounts of data and help to detect anomalies. Such systems reduce the workload on security teams and improve the accuracy and speed of threat response. Special attention is given to the analysis of modern AI-powered antivirus solutions, particularly Microsoft Defender for Endpoint and Darktrace. These solutions are based on behavioral analysis algorithms and machine learning, allowing for more effective detection of complex threats and incident prevention. Microsoft Defender provide a high level of endpoint protection. Meanwhile, Darktrace utilizes self-learning models to analyze network traffic, enabling the detection of zero-day threats and internal risks within organizations. The study also learns the major risks associated with the use of AI in cybercrime. AI is increasingly leveraged by malicious actors to automate attacks, significantly increasing their effectiveness and making detection more challenging. The primary AI-based cyber threats discussed include Data Poisoning attacks, Evasion Attacks, Prompt Injection Attacks, and AI-based social engineering. To mitigate these risks, the development of robust AI models resistant to adversarial attacks, increased algorithm transparency, and implementation of the International AI regulation standards is recommended, including NIST. Additionally, raising awareness among users and cybersecurity specialists is crucial, as the human factor remains one of the most significant vulnerabilities in security systems. In conclusion, it is said that AI is a key factor in the advancement of cybersecurity, offering significant improvements in protecting information and critical systems. However, without proper regulation and protective measures, AI can become a powerful tool for cybercriminals, posing new security challenges in the digital age. Striking a balance between innovation, ethical standards, and security will be essential in shaping the future strategy for the effective use of AI.